Kajian Peningkatan Aktivitas Antioksidan pada Umbi-Umbian Melalui Fermentasi - Nur Hasanah Jusman; Prima Retno Wikandari; Ratih Dewi Saputri (Universitas Djuanda, 2025)
Tubers are recognized as local food sources rich in bioactive compounds, particularly phenolics and flavonoids, which function as natural antioxidants. However, in many tubers, phenolic compounds are often bound in glycosidic forms, reducing their antioxidant effectiveness. To enhance their bioactivity, these glycosidic bonds can be hydrolyzed through fermentation, utilizing microorganisms with β-glucosidase activity such as Lactobacillus plantarum. This enzyme breaks glycosidic bonds, releasing glucose and aglycones in free forms that are more biologically active and possess greater antioxidant potential. As a result, the bioavailability and absorption of phenolic compounds in the human body are improved, enhancing their ability to neutralize free radicals. Several types of tubers, including Chinese yam, jicama, and cassava, have shown significant increases in total phenolic and flavonoid content after undergoing fermentation. Studies have demonstrated that fermentation not only boosts antioxidant activity but also supports the development of more nutritious and affordable functional food products derived from tubers. Nonetheless, the success of fermentation depends on several factors, including microbial strains, fermentation duration, environmental conditions, and processing techniques. This review aims to summarize current findings on how fermentation enhances antioxidant properties in tubers and its potential application in functional food innovation.